2013
DOI: 10.4161/gmic.27492
|View full text |Cite
|
Sign up to set email alerts
|

A novel SCFA receptor, the microbiota, and blood pressure regulation

Abstract: T he maintenance of blood pressure homeostasis is a complex process which is carefully regulated by a variety of inputs. We recently identified two sensory receptors (Olfactory receptor 78 and G protein couple receptor 41) as novel regulators of blood pressure. Both Olfr78 and Gpr41 are receptors for short chain fatty acids (SCFAs), and we showed that propionate (a SCFA) modifies blood pressure in a manner which is differentially modulated by the absence of either Olfr78 or Gpr41. In addition, propionate modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
258
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(269 citation statements)
references
References 66 publications
1
258
0
10
Order By: Relevance
“…2, estimated from data analyzed by the Rat Genome Database; http:// www.rgd.mcw.edu). Since there are no variants in the homologous rat genes for Olfr78 and Gpr41, the two mouse genes reported for gut microbial links to hypertension (38), it is reasonable to conclude that variation within host genomic factors, which are not within Olfr78 and Gpr41, are likely influencing microbiotal compositions of S and R rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, estimated from data analyzed by the Rat Genome Database; http:// www.rgd.mcw.edu). Since there are no variants in the homologous rat genes for Olfr78 and Gpr41, the two mouse genes reported for gut microbial links to hypertension (38), it is reasonable to conclude that variation within host genomic factors, which are not within Olfr78 and Gpr41, are likely influencing microbiotal compositions of S and R rats.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the gut microbiota to influence BP is limited. To date, there are two studies reported (38,41), which were specifically focused on data obtained from an olfactory G protein-coupled receptor (Olfr78) and G protein-coupled receptor (Gpr41) knockout mice. To our knowledge, there are no gut microbiotal studies reported in genetic models of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 In addition, the production of short-chain fatty acids by the gut microbiota can affect blood pressure by interaction with renal sensory nerves and an increase in renin secretion. 63,64 Perhaps, more importantly, gut microbiota, particularly with regard to intestinal wall inflammation, has been linked to the presence and severity of systemic inflammation. Several studies have shown that the level of Gram-negative bacteria endotoxin and bacterial DNA fragments in the systemic circulation are correlated with increased plasma CRP, IL-6 and D-lactate.…”
Section: Inflammation and Hypertension Y Solak Et Almentioning
confidence: 99%
“…Propionate, one of the SCFA, activate the Gpr41 leads to a hypotensive response and enable the Olfr78 favors a hypertensive response via renin release mediated by cAMP production. However, these effects are abolished in Olfr78 and Gpr41-deficient mice, as well as an antibiotic-treated mice [38]. H 2 S is also a microbiota metabolite, an important biological mediator involved in the various process include hypertension [39].…”
Section: Possible Mechanisms: How the Gut Microbiota Regulating Hypermentioning
confidence: 99%